Associations Between Iron Deficiency Anemia and Wages in India: A Secondary Data Analysis (P22-016-19). (13th June 2019) - Makkar, Sanchit; Minocha, Sumedha; Bhat, Kishor; John, Anjaly; Swaminathan, Sumathi; Thomas, Tinku; Mannar, Venkatesh; Kurpad, Anura
Abstract: Objectives: Economic analyses add value beyond evidence to the implementation of any policy. The study explored the association between iron deficiency anemia (IDA) and the wages of adult men and women between 15- 49 years in India so that the possible monetary benefits of iron fortification policies could be evaluated. Methods: National sample survey organization (NSSO) Employment- Unemployment data was statistically matched with the NSSO Consumer Expenditure data at an individual level for the year 2011–12. The anemia levels (assuming 50% of anemia was due to iron deficiency) was mathematically modelled in response to a wide range of nutrient intakes, including iron intake from heme and non-heme sources along with inhibitors and enhancers in the diet, adjusting for bioavailability, sanitation and menstrual losses in women. A two-stage Heckman selection model was used to establish the association between wages and IDA. In the first stage, a probit model was used to determine labour force participation and in the second stage, an ordinary least square model, corrected for sample selection bias, was used to determine the impact of IDA on wages. Results: The presence of IDA resulted in a decline of 15.3 percentage points in wages of regular salaried employed men as compared to those without IDA. Similar patterns was observed for women but the impact of anemia on wages was lower in comparison to men. Among women, a decline of 8.0 percentage points was observed in the wages of regular salaried employed women compared to those without IDA. However, the presence of IDA had no significant impact on the wages of casual labourers. This indicated that there were other random factors that affected the wages of this segment of population. Conclusions: There is an association between IDA and wages for a segment of working population. Addressing anemia through iron fortification programs such as the usage of double fortified salt could possibly change living standards of the population through improvement in earnings. Funding Sources: International Development Research Centre, Canada; Tata Trusts, India.